Long-term nutrient management in an intensive rice-wheat cropping system improves the quantities, qualities, and availability of soil sulfur - Meena, Sunita Kumari; Dwivedi, B. S.; Meena, Mahesh C.; Datta, S. P.; Singh, Vinod Kumar; Mishra, R. P.; Chakraborty, Debashish; Dey, Abir; Meena, Vijay Singh (Frontiers in Sustainable Food Systems, 2022)
In the last few decades, the deficiency of sulphur (S) has been noticed in agricultural soils of India. Meanwhile, researchers reported that S play a significant role in the productivity of rice-wheat cropping system (RWCS). To quantification of S response, a long-term field experiment was started at ICAR-IIFSR, Modipuram, India. Seven nutrient supply options were applied organic, mineral fertilizer in combination of IPNS, IPNS + B/IPNS + C in the S availability of the soil in the RWCS. Results showed that highest contribution in S availability by the total-S (39%) followed by the organic-S (35%), NaHCO3-ES (7%), heat SS (7%), WSS (4%), available-S (4%) and inorganic-S (4%) under different long-term nutrient supply options of RWCS. The continuous application of organic fertilizer and various IPNS options such as the inclusion of pulses significantly improved all S fractions in the soil, also offers an additional benefit in terms of sustainability of production and soil health compared to the inorganic fertilizer fields. Overall, results showed that IPNS showed its superiority over the rest of the treatment. Results also supported that the inclusion of pulses gives further gain in terms of sulphur availability in soil system under RWCS.